About trend in zinc stellar abundances with metallisity - Bayazitov, U. Sh.; Thevenin, F. (Одеські астрономічні публікації, 2007)
We have carried out investigation of zinc abundance behavior in wide range of stellar metallicities from 0 to -5. It has been determined zinc abundance using our Zn atom model and NonLTE calculation method. It has been shown that difference between LTE and NonLTE Zn abundances may reached up to 1.27dex.We have obtained the dependence of [Zn=H] from [Fe=H]. The first value is greater as metallicity lower.